25-GAUGE PARS PLANA VITRECTOMY AND SF6 GAS FOR THE REPAIR OF PRIMARY INFERIOR RHEGMATOGENOUS RETINAL DETACHMENT. Issue 6 (June 2016) - Duvdevan, Nitsan; Mimouni, Michael; Feigin, Elena; Barak, Yoreh
Abstract : Purpose: To compare anatomical and functional outcomes of 25-gauge pars plana vitrectomy (PPV) and sulfur hexafluoride gas between inferior and superior rhegmatogenous retinal detachment (RRD). Methods: A retrospective cohort study of patients with RRD who underwent 25-gauge PPV. Group A consisted of patients with an identified inferior retinal break (4–8 o'clock hours). Group B consisted of patients with an identified superior retinal break. Results: Overall, 59 eyes of 59 patients with a mean age of 60.0 ± 12.3 years were included, with 57.6% being males; 25 with inferior breaks (Group A) and 34 with superior breaks (Group B). The mean follow-up time was 4 months (range 2–16 months). Single-surgery anatomical success was achieved in 96% (24/25) of Group A and 82.4% (28/34) of Group B patients ( P = 0.22) with final anatomical success achieved in all cases. In regression analysis, break location (superior versus inferior) did not significantly account for the variation in single-surgery success or visual outcomes. Conclusion: Favorable results were achieved using 25-gauge vitrectomy and sulfur hexafluoride gas for primary RRD treatment. No differences in anatomical and functional success rates were observed between inferior and superior retinal break-associated RRD. Abstract : The primary anatomic success rate and visual outcome of rhegmatogenous retinal detachment with inferior breaks versus superior breaks is similar when treating with 25-G pars plana vitrectomy combined with 25% sulfur hexafluoride gas. This buckle-free procedure produces a 96% single surgery anatomical success while avoiding the additional risks of a buckle.